Information and Communication Technology in the World of Education: A Theoretical and Empirical Overview – A Literature Review - Sibagariang, Susy Alestriani; Pohan, Fitriana; Lubis, M. Joharis; Zainuddin, Zainuddin (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
In an era where digital technology is pivotal, the integration of Information and Communication Technology (ICT) in education has become a focal point of research and discussion. This comprehensive literature review aims to bridge the gap in understanding the multifaceted impact of ICT on educational paradigms. The study delves into the transformative influence of ICT on teaching methodologies, the democratization of educational access, and the overall quality of learning experiences. Methodologically, this review synthesizes diverse academic sources, including empirical studies, theoretical frameworks, and case analyses. By integrating a broad spectrum of research findings, it provides a holistic view of the evolving educational landscape shaped by ICT. The study adopts a critical approach, weighing the advantages against the inherent challenges of ICT in education. The main findings reveal that ICT has revolutionized educational practices by introducing innovative teaching tools and methodologies. Digital platforms and resources have facilitated a more interactive, student-centered learning environment, enhancing engagement and comprehension. Moreover, ICT has played a crucial role in democratizing education, providing greater access to learning resources and opportunities, especially in underprivileged and remote areas. This aspect of ICT aligns with global educational equity goals, aiming to bridge the digital divide and create a more inclusive educational system. The review concludes that while ICT offers substantial benefits in reshaping education, a strategic and balanced approach is necessary. This approach should focus on mitigating digital inequality, ensuring continuous professional development for educators, and fostering an environment conducive to the effective integration of ICT. Future research directions include exploring the long-term impacts of ICT in education, particularly in developing countries, and examining the sustainability of technology-driven educational models.